2008
DOI: 10.1248/bpb.31.1115
|View full text |Cite
|
Sign up to set email alerts
|

Satratoxin H Generates Reactive Oxygen Species and Lipid Peroxides in PC12 Cells

Abstract: Satratoxin H, a mycotoxin, is thought to induce apoptosis of PC12 cells through the activation of p38 mitogen-activated protein kinase (MAPK) and c-Jun N-terminal kinase (JNK) in a glutathione (GSH)-sensitive manner. The present study was undertaken to further elucidate the mechanism by which satratoxin H induces cell death in PC12 cells. Satratoxin H caused apoptosis of PC12 cells within 24-h, as determined by DNA fragmentation and flow cytometric analysis. Satratoxin H increased reactive oxygen species (ROS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 53 publications
3
11
0
1
Order By: Relevance
“…Numerous researchers have shown that ROS relate to apoptosis that is processed through the mitochondrial pathway, which depends on the activation of p38 (Figure 2) [40][41][42][43][44] . Apoptosis signal-regulating kinase 1 (ASK1) is an evolutionarily conserved mitogenactivated protein 3-kinase that activates both JNK and p38 MAPK, which may also be triggered by ROS [45][46][47][48][49] .…”
Section: Ros Involve Apoptosis That Relates To the P38 Pathwaymentioning
confidence: 99%
“…Numerous researchers have shown that ROS relate to apoptosis that is processed through the mitochondrial pathway, which depends on the activation of p38 (Figure 2) [40][41][42][43][44] . Apoptosis signal-regulating kinase 1 (ASK1) is an evolutionarily conserved mitogenactivated protein 3-kinase that activates both JNK and p38 MAPK, which may also be triggered by ROS [45][46][47][48][49] .…”
Section: Ros Involve Apoptosis That Relates To the P38 Pathwaymentioning
confidence: 99%
“…Previously, we demonstrated that satratoxin H caused the apoptosis in PC12 cells with the IC 50 of approximately 50 nM through MAPK (Nusuetrong et al, 2005) and ROS generation (Nusuetrong et al, 2008). We further showed that satratoxin H induced DNA fragmentation in PC12 cells (Nusuetrong et al, 2008).…”
Section: Introductionmentioning
confidence: 78%
“…We further showed that satratoxin H induced DNA fragmentation in PC12 cells (Nusuetrong et al, 2008). However, although DNA is triggered single-stranded or double-stranded breaks, a mechanism of satratoxin H on DNA damage is unknown.…”
Section: Introductionmentioning
confidence: 80%
“…Satratoxin H is thought to induce apoptosis of PC12 cells through the activation of p38 mitogen activated protein kinase and c-Jun N-terminal kinase in GSH-sensitive manner [173]. Chemoprotective effects of flavonoid compounds against aflatoxins were confirmed in hens [174].…”
Section: Mmycotoxins and Apoptosismentioning
confidence: 97%